The impact of efficiency on asset quality in banking. Issue 6 (13th April 2022) - Badunenko, Oleg; Dadoukis, Aristeidis; Fusi, Giulia; Simper, Richard
ABSTRACT: We investigate the impact of banks' ability to minimise costs on asset quality, by assessing the temporal relationship between these variables in a sample of Italian banks over the period 2006–2015. We offer new insights into the channels through which bank efficiency affects non-performing loans by disentangling the short-term component of cost efficiency from its long-term component. We show that non-performing loans afflicting Italian banks can be explained by both efficiency components. A decrease in short-term cost efficiency precedes a worsening in banks' asset quality, implying that regulators should consider adopting short-term efficiency as an early warning indicator of a deterioration in asset quality. We also present evidence of a trade-off between long-term efficiency and bank non-performing loans, which suggests that the removal of exogenous hindrances that prevent banks from allocating optimal levels of resources to the management of their loan portfolio should be a main policymakers' objective.